Management Of Akad Murabahah On Subsidized Housing Financing In The Branch Office Of Bank Tabungan Negara (BTN) Sharia In Batam - Wibisono, Chabullah; Purwanti, Ipunk (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2018)
One type of bank product is a mainstay now is the form of offering financing products Ownership Subsidized Housing, And needs of the community, especially the lower middle-class society will be the availability of housing that is habitable is a primary need that can not be rejected again. For that form of mortgage financing for most people is the best solution. However, a problem arises where there has been much disagreement on the principles of sharia. In other words, in the have a â€œmuamalahâ€ activities should use the provisions in force in the field of Islamic law. The provisions of Islamic law governing the movements between the man known as the principles of sharia have an essential role in the economic life of society. The purpose of which is to meet community needs for housing or decent housing. The manifestation of professionalism shown by the Branch Office â€œmuamalahâ€ in Batam achieve it best category award in the realization of Subsidized Housing Nasional. Bank level BTN Sharia also always provide the best service to its customers, which one of them through subsidized homeownership financing in sharia and always follow legislation in force. Based on the analysis and the previous discussion, the following authors put forward some conclusions as follows: a. The need for residential facilities is essential for all Indonesian citizens without feathers . By of view because it is the muamalahtake on this important role as a pioneer of home finance is subsidized. All that aims to provide a sense of justice and improve the welfare of society. b. In the subsidized homeownership financing in Islamic Party muamalahBranch Office of Batam and the recipient of the funding first, make â€œwakalahâ€ which stated that the client authorizes the bank to build a home purchase subsidy desirable customers. Then in use â€œwakalahâ€, and the bank buys the house from the developer. After the purchase of the house and then the banks did purchase contract to the customer at the selling price agreed upon after the added margin (profit) bank. This is what is called a transaction â€œMurabahahâ€. Then customers pay the installments corresponding periods in multi separate.Transaksi this contract are allowed by the National Sharia Board fatwa Indonesian Ulema Council with the provisions of Indo- No.10/DSN-MUI /IV/ 2000 on â€œwakalahâ€. In the implementation of the financing agreement are carried out by the â€œmuamalahâ€ Branch Office with the recipient Batam financing problems may occur. Problems or problematic were generally occurred because of the faith that is not good from the receiving party financing. Said that because the â€œmuamalahâ€ Branch Office will hold a time Batam financing agreement has been briefed in detail the contents of the contract is communicated to the recipient of financing. The problems that occurred in the implementation of â€œMurabahahâ€ in subsidized homeownership financing in sharia at the muamalah Branch Office (BTN) Sharia in Batam generally consist of two (2) types, namely: a. Recipients of subsidized home ownership financing by sharia late paying the installments that exceed the agreed time limit. b. Rececier subsidized home ownership financing by sharia are unable to pay the number of episodes as agreed.Keywords:Â Management, Akad Murabahah,Â Subsidized Housing, Sharia Bank.